Gender and African indigenous religions - Dube, Musa Wenkosi; Musili, Telesia K.; Owusu-Ansah, Sylvia (Routledge, 2024)
"Focusing on the work of contemporary African women researchers, this volume explores feminist perspectives in relation to African Indigenous Religions (AIR). It evaluates what the Circle of Concerned African Women Theologians' research has achieved and proposed since its launch, their contribution to the world of knowledge and liberation, and the potential application to nurturing a justice-oriented world. The book considers the methodologies used amongst the Circle to study African Indigenous Religions, the AIR sources of knowledge that are drawn on, and the way in which women are characterized. It reflects on how ideas drawn from African Indigenous Religions might address issues of patriarchy, colonialism, capitalism, racism, tribalism, sexual and disability-based discrimination. The chapters examine how a specific figure's theology converses with Global South theologies, and Western feminist theologians. The book will be of interest to scholars of religion, gender studies, Indigenous studies, and African studies"--